Use of Halfa Bar Essential Oil (HBO) as a Natural Growth Promoter in Broiler Nutrition - Amal, O.A.; Mukhtar , A.M.; Mohamed, K.A.; Ahlam, A.H. (International Journal of Poultry Science, 2012)
This experiment was conducted to evaluate the response of broiler chicks to diets containing graded levels of essential oil extracted from Halfa Bar Oil (HBO). A total of 160, five days-old, unsexes (Ross 308) broiler chicks were used. Chicks were weighed individually and assigned randomly to five groups of 32 chicks per treatment and each treatment group consisted of four replicates of 8 chicks per each. Five experimental diets were formulated (A, B, C, D and E) to meet the nutrient requirements. The experimental parameters covered growth performance, carcass characteristics serum metabolite, electrolyte and enzyme activities. Diets A as Negative Control (NC), diet B control diet supplemented with antibiotic (Neomycin 16 mg/Kg) as Positive Control (PC), diets C, D and E were NC supplemented with Halfa Bar Oil (HBO) at 50, 100 and 150 mg/Kg, respectively. Result obtained showed that addition of HBO improved significantly (P<0.05) the performance (body weight gain, feed intake and feed conversion ratio) of broiler chicks compared to group fed on NC while no Significant (P<0.05) differences between chicks fed on diets supplemented with HBO and PC group observed. The mortality rate did not influenced by the dietary treatments. Results revealed no significant differences (P<0.05) among all treatment groups in the percentages of carcass dressing, giblet, commercial cuts and their percentage of their separable tissue, meat chemical composition and subjective meat quality parameters. Supplementation of HBO in the broiler diets at various levels resulted in significant (p>0.05) reduced of serum cholesterol, urea and ALP enzyme activity compared to both NC and PC groups while the level of total protein, calcium, phosphorus and AST remained unchanged. Economically the addition of HBO improved the performance of broiler chicks and resulted in economical benefits. This study showed that HBO when added as growth promoter in broiler diets has a similar effect as that with antibiotic without any adverse effects.